Pengaruh Volatilitas Penjualan Dan Siklus Operasi Terhadap Persistensi Laba Melalui Non Discretionary Accrual (Studi Pada Perusahaan Property Dan Real Estate Yang Terdaftar di BEI Tahun 2016-2020) - Naslia Naslia; Jamaluddin Majid (Indonesian Journal of Taxation and Accounting, 2023)
This study aims to examine the effect of sales volatility and the operating cycle on earnings persistence through non-discretionary accruals in property and real and estate companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research is a quantitative research with a comparative causality approach. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange with purposive sampling technique. The data used in this study is secondary data which is accessed through www.idx.co.id. Data analysis uses path analysis and uses the Sobel test to examine the indirect effect of sales volatility and the operating cycle on earnings persistence through non-discretionary accruals. The results showed that sales volatility had no effect on non-discretionary accruals, while the operating cycle had an effect on non-discretionary accruals, sales volatility and the operating cycle had an effect on earnings persistence and non-discretionary accruals had an effect on earnings persistence. Meanwhile, the results of the indirect or mediating effect test show that non-discretionary accruals are only able to mediate the operating cycle on earnings persistence